O Sistema colaborativo como dispositivo gerador de empregabilidade - Santos, Adilson José dos (2020)
The present work addresses the study of social networks and how they can be used as tools that generate employability. In his theoretical approach, he addressed the current job market, employability and collaborative networks, identifying the importance of information for employability. Its main objective was to develop a collaborative network system on a responsive platform that serves as a tool for the integration of its users aiming at achieving employability. As a research product, it resulted in collaborative software in the form of a social network, with the purpose of facilitating employability. The Software makes it possible to access job vacancies by sharing the knowledge of the network's own users in the form of posts, which can be recommended to other users and commented on by others, enabling two-way communication and generating greater interaction between those involved. The System also provides users with access links to the job search features available on the social networks most used by Brazilians. The software was specified using the main concepts of UML and developed using PHP language and MySQL relational database, combined with other open source technologies. It was concluded that, as it is a platform aimed at promoting employability in a collaborative way, it has a favorable social impact and wide visibility, further offering courses for continuing education. In terms of technological innovation, the development of the platform presented as a product a software with a wide reach of accessibility, ease of use of search and solution to the demands of its users.